Financial and organizational foundations of economic entities' ecologically oriented activities - Тулвй, Оксана Іванівна (My University, 2017)
Research topic relevance. Modern financial and economic activities of business entities aimed at obtaining economic benefits and increasing current and future cash flows can lead to the destruction of non-renewable natural resources, which are a prerequisite for the existence of life. Problem setting. Today in Ukraine the issue of financial incentives and motivation for subjects of economic relations to carry out environmental measures is getting more public attention. Recent research and publications analysis. Theoretical and methodological principles of nature conservation activities are reflected in the works of R. Burling, V. Vernadsky, V. Gavran, E. Libanova, A. Ness, A. Pigou, S. Podolinsky, K. Shilin and others. Selecting unexplored parts of the general problem. Nevertheless, the issues of formation of financial and organizational preconditions of ecologically oriented activities of domestic business entities remain unsolved. Objective setting. The purpose of the publication is to outline the financial and organizational foundations of environmentally oriented activities of business entities in the context of sustainable human development ideology. Main material presentation. The article substantiates the necessity of making economic systems more ecologically friendly. It analyses the problem aspects of financing nature conservation activities in Ukraine. The research also shows the specifics of ecological taxation as an effective financial instrument for the implementation of the state environmental policy. Conclusions. In order to prevent the fatal impact of technological progress on the environment, economic entities need to increase their environmental protection costs. Being an effective financial tool for stimulating investment and innovation activities in the field of environmental protection, ecological taxation contributes to raising the levels of environmental safety and social security of the people
Keywords: environmental protection financing, ecological taxation, ecological policy, sustainable human development